Hygiene standards in food processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Sidi Fofana, coordinator and trainer at the Banjulunding food processing plant in The Gambia explains the detailed procedures needed to maintain hygiene in the plant.